2014
DOI: 10.1016/j.jdeveco.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Sequential lending with dynamic joint liability in micro-finance

Abstract: This paper develops a theory of sequential lending in groups in micro-finance that centers on the notion of dynamic incentives, in particular the simple idea that default incentives should be relatively uniformly distributed across time. In a framework that allows project returns to accrue over time, as well as strategic default, we show that sequential lending can help resolve problems arising out of coordinated default, thus improving project efficiency vis-a-vis individual lending. Inter alia, we also provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Furthermore, beneficiary banks in some cases adopt a group-based lending approach like the one adopted widely in micro-credit programs to reduce the default risk (Jointliability mechanism works successfully as a safeguard against credit default in many microcredit programs, particularly in Bangladesh [27,28]. Therefore, these two criteria of selecting borrowers-an SMEF beneficiary and being a part of group-based lending-reduce the asymmetry of information about the borrowers and increases the probability of loan repayment significantly.…”
Section: The Cw Programmentioning
confidence: 99%
“…Furthermore, beneficiary banks in some cases adopt a group-based lending approach like the one adopted widely in micro-credit programs to reduce the default risk (Jointliability mechanism works successfully as a safeguard against credit default in many microcredit programs, particularly in Bangladesh [27,28]. Therefore, these two criteria of selecting borrowers-an SMEF beneficiary and being a part of group-based lending-reduce the asymmetry of information about the borrowers and increases the probability of loan repayment significantly.…”
Section: The Cw Programmentioning
confidence: 99%
“…Although there has been a movement towards individual lending over the past decade or so, group lending has been widely adopted by MFIs worldwide (Abbink et al, 2006; Chowdhury et al, 2014). The popularity of group lending can be explained by its reach to more people, thus widening the benefits to the wider community.…”
Section: Introductionmentioning
confidence: 99%
“…Ahlin and Townsend (2007) study in Thailand revealed that the close bond and regular interaction between the group loan members can conceal important project information from the lender, impede social sanctions and promote collusion. All group members can work together to default on repayments and shield one another from the social pressure coming from the wider community (Chowdhury et al, 2014). While Mustakallio et al (2002) refers to close ties as family links, the definition and measurement of tie strength have not been specified in the work of (Ahlin & Townsend, 2007; Dufhues et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Joint-liability mechanism works successfully as a safeguard against credit default in many microcredit programs, particularly in Bangladesh(Chowdhury, Chowdhury, and Sengupta 2014;Pitt and Khandker 2002).…”
mentioning
confidence: 99%